Do economic and non-economic factors determine village fund in the 4.0 industrial revolution regime? - Lely Ratwianingsih; Mulyadi Mulyadi; Malik Cahyadin; Yunastiti Purwaningsih (Faculty of Economics and Business Mulawarman University, 2021)
This research aims to identify the economic and non-economic factors which are perceived by the community to be able to determine Village Fund in Central Java. The data were collected from surveys to village governments in 29 regencies in Central Java (with a total of 70 observed respondents), which were then analyzed using AHP and SWOT methods. This research concludes that there are 8 economic and 5 non-economic factors which determine the Village Fund. They are divided into internal and external. The internal factors determining the Village Fund consist of among others: strength (utilization of village’s human resource and natural resource potential; village-owned enterprises development; community welfare; active community participation; good economic activity; lack of knowledge and initiative from village officials; lack of village fund governance; and, low allocation for economic and community empowerment). Meanwhile, the external factors determining the Village Fund are opportunities (support from central regional government, village stakeholders’ potential contribution, local products’ market expansion, and threats (foreign cultural influences through ICTs), environmental impact, and competition between villages. All those factors are related to the Government’s efforts to direct all the villages’ resources potential in accordance with the dynamics of the 4.0 Industrial Revolution. The significant contribution of this research is the finding that Village Fund should facilitate woman economic empowerment and family welfare.